Energy Harvesting Multi-Relay Multi-Hop Models For Sustainable Wireless Sensor Network - Arya, KS; Manojkumar, PK (International Journal of Computer Sciences and Engineering, 2025)
The load inequality of sensor node is a relentless issue for Wireless Sensor Networks (WSNs). In this paper, we firstly propose a Multi-hop Multi-relay Network Model (MMNM) with Relaying Head (RH) to balance the load among sensor nodes. The evolution of recent energy harvesting delivers us the Energy accumulation Wireless Sensor Networks (EH-WSNs). Due to the indeterminacy of energy that can be harvested in ambient environment, study on energy management mechanism to achieve energy neutral is significant. We proposed a novel Sensor Nodes Pair (SNP) policy separate all the sensor nodes into two groups GSN and GSN’. With the function rotation of GSN and GSN’, we achieve continuous data transmission avoiding time delay. Also a Historical Harvested Energy Assigning Mechanism (H-HEAM) is proposed to ensure the energy neutral constrains and perpetual network operation. Extensive simulation results verify that our MMNM and H-HEAM are indeed able to improve the network overall performance on throughput, energy utilization efficiency and time delay